Exercise For Pregnancy and Beyond - Jones-Boswell, Elizabeth (USA Elizabeth Jones-Boswell, 2005)
Pilates-based approach to pregnancy exercise and postpartum exercxise
Keywords: Pregnancy -- Exercise -- Pilates